Investigation of the superconducting energy gap in the compound LuNi₂B₂C by the method of point contact spectroscopy: two-gap approximation - Bobrov, N.L.; Beloborod’ko, S.I.; Tyutrina, L.V.; Chernobay, V.N.; Yanson, I.K.; Naugle, D.G.; Rathnayaka, K.D.D. (Физика низких температур, 2006)
It is shown that the two-gap approximation is applicable for describing the dV/dI(V) spectra
of LuNi₂B₂C–Ag point contacts in a wide interval of temperatures. The values and the temperature
dependences of the large and the small gaps in the ab plane and in the c direction were estimated
using the generalized BTK model [A. Plecenik, M. Grajacar, S. Benacka P. Seidel, A. Pfuch,
Phys. Rev. B49, 10016 (1994)]] and the equations of [S.I. Beloborodko, Fiz. Nizk. Temp. 29, 868
(2003) [Low Temp. Phys. 29, 650 (2003)]. In the BCS extrapolation the critical temperature of
the small gap is 10 K in the ab plane and 14.5 K in the c direction. The absolute values of the gaps
are ∆₀ab = 2.16 meV and ∆₀с = 1.94 meV. For the large gaps the critical temperature Tc coincides
with the bulk, Tc = 16.8 K, and their absolute values are very close, being about 3 meV in both
orientations. In the c direction the contributions to the conductivity from the small and the large
gaps remain practically identical up to 10–11 K. In the ab plane the contribution from the small
gap is much smaller and decreases rapidly as a temperature rises.